Evaluation of DNA typing as a positive identification method for soft and hard tissues immersed in strong acids. Issue 6 (November 2015) - Robino, C.; Pazzi, M.; Di Vella, G.; Martinelli, D.; Mazzola, L.; Ricci, U.; Testi, R.; Vincenti, M.
Graphical abstract: Highlights: We evaluated DNA typing in soft/hard tissue samples immersed in strong acids. A porcine animal model was used for DNA quantitation and STR typing. Time span for genetic identification of teeth is on a par with that of dental methods. Genetic identification of bone samples is possible after prolonged acid treatment. Time span for genetic identification of bones exceeds that of morphological methods. Abstract: Identification of human remains can be hindered by several factors (e.g., traumatic mutilation, carbonization or decomposition). Moreover, in some criminal cases, offenders may purposely adopt various expedients to thwart the victim's identification, including the dissolution of body tissues by the use of corrosive reagents, as repeatedly reported in the past for mafia-related murders. By means of an animal model, namely porcine samples, we evaluated standard DNA typing as a method for identifying soft (muscle) and hard (bone and teeth) tissues immersed in strong acids (hydrochloric, nitric and sulfuric acid) or in mixtures of acids (aqua regia). Samples were tested at different time intervals, ranging between 2 and 6 h (soft tissues) and 2–28 days (hard tissues). It was shown that, in every type of acid, complete degradation of the DNA extracted from soft tissues preceded tissue dissolution and could be observed within 4 h of immersion. Conversely, high molecular weight DNA amenable to STR analysis could be isolated from hard tissues as long as cortical bone fragments were still present (28 days for sulfuric acid, 7 days for nitric acid, 2 days for hydrochloric acid and aqua regia), or the integrity of the dental pulp chamber was preserved (7 days, in sulfuric acid only). The results indicate that DNA profiling of acid-treated body parts (in particular, cortical bone) is still feasible at advanced stages of corrosion, even when the morphological methods used in forensic anthropology and odontology can no longer be applied for identification purposes.